Faktor-Faktor yang Berhubungan Dengan Mortalitas dan Morbiditas pada Pasien Geriatri yang Menjalani Prosedur Anestesi Di RSUP Dr. Sardjito - Arifin, Achmad Reza; Widyastuti, Yunita; Sudadi (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2022)
Background: Geriatrics is defined as someone who reaches the age of 60 years and over. With the increase in the level of the economy and health, the geriatric population will increase. So that surgery and anesthesia in geriatric patients also increased. Geriatric patients tend to have more comorbidities accompanied by a decrease in physiological function and cognitive function so that it has an impact on mortality and morbidity. Objective: To identify the factors related to mortality and morbidity in geriatric patients undergoing anesthesia procedures at Dr. Sardjito General Hospital. Method: This study was conducted in a prospective analytical observational to identify risk factors in geriatric patients undergoing anesthesia at Dr. Sardjito General Hospital. The affordable population was all geriatric patients aged 60 years and over, who underwent anesthesia in the operating room and the time of the study was carried out for 3 months. In this study, variables that are thought to have a relationship with mortality and morbidity of geriatric patients will be tested using a univariate test using the Student's t-test if the data is numerical, while if the data is categorical using the Chi Square test. If the results of p<0.25 will be continued with the logistic regression test of each variable. And if p<0.05 then the variable is included in the multivariate analysis and if p<0.05 is considered significant. Results: The factors identified as factors affecting mortality of geriatric patients undergoing anesthesia at Dr. Sardjito General Hospital are age ≥75 years, dementia, and digestive surgery with p <0.05 in both univariate and multivariate tests. In the multivariate logistic regression test, factors affecting morbidity of geriatric is digestive surgery with p < 0,05. Conclusion: Patients’ age≥75 years, dementia and digestive surgery are the identified factors affecting mortality and morbidity of geriatric patients undergoing anesthesia at Dr. Sardjito General Hospital.